Platinum-conductive diamond composite antipolar catalyst, method of making and fuel cell

CN122889771APending Publication Date: 2026-10-09GUANGZHOU DEPOSON ELECTRIC TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611179102.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-05-31
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]这种传统材料存在很大缺点: 所担载活性物质的碳基类载体易在高电位或燃料电池反极状态下被腐蚀进而引起活性物质脱落和团聚,引起电池性能下降

Benefits of technology

以导电金刚石作为载体或催化剂添加剂,实现反极高电位下的优先水电解以抑制碳腐蚀的功能,比起昂贵稀少的铱、钌类贵金属及其氧化物,导电金刚石可人工合成,实现大规模的商业应用,使得燃料电池的推广应用更具可能性,且成本低廉;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889771A_ABST
    Figure CN122889771A_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a platinum-conductive diamond composite anti-reverse catalyst, which comprises the following steps: S1, providing one or more of nano diamond particles, nano boron nitride, nano boron carbide, metal oxide nano particles, metal carbide nano particles, metal nitride nano particles and silicon-based nano particles as a nano particle base, or forming a porous structure on the surface of the nano particles to obtain the nano particle base; S2, assembling conductive diamond particles on the nano particle base to obtain a nano sapphire combination; S3, providing at least one of carbon-supported platinum particles and carbon-supported platinum alloy particles and mixing the nano sapphire combination, or providing a carbon-based carrier, mixing the nano sapphire combination and the carbon-based carrier to obtain a mixed particle carrier, loading platinum and / or platinum alloy nano particles on the surface of the mixed particle carrier, or loading platinum and / or platinum alloy nano particles on the surface of the nano sapphire combination to obtain the platinum-conductive diamond composite anti-reverse catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fuel cell materials, and more particularly to catalyst materials for proton exchange membrane fuel cells. Background Technology

[0002] As a novel type of electrochemical energy converter, fuel cells enable the reactants at both the anode and cathode to rapidly convert chemical energy into electrical energy while exceeding the efficiency limits of the Carnot cycle. Proton exchange membrane fuel cells (PEMFCs) are considered the earliest commercially viable type of fuel cell due to their rapid start-up response, low operating temperature, and modular stacking capability.

[0003] The energy conversion component of a proton exchange membrane fuel cell is the membrane electrode assembly (MEA), in which the core energy conversion material is a catalyst layer composed mainly of catalyst and proton exchange resin. Currently, catalysts close to large-scale commercialization consist of nano-platinum or platinum alloy active materials supported on carbon-based supports, exhibiting extremely rapid electrocatalytic activity for both the anode (hydrogen oxidation reaction) and the cathode (oxygen reduction reaction).

[0004] This traditional material has significant drawbacks: the carbon-based support for the active material is susceptible to corrosion under high potential or reverse polarity conditions in fuel cells, leading to active material shedding and aggregation, and consequently, a decline in battery performance. Furthermore, the high-temperature graphitization treatment of carbon-based supports, typically used to increase their high-potential stability, makes them relatively hydrophobic. This causes the anode catalyst layer to easily lose water under the relatively dry conditions of the fuel cell, resulting in increased internal resistance and decreased battery performance. Meanwhile, while introducing precious metals such as iridium and ruthenium, and their oxides, into proton exchange membrane water electrolysis systems can preferentially oxidize water under reverse polarity conditions to temporarily mitigate the oxidative corrosion of the carbon-based support, the extreme scarcity of iridium and ruthenium severely hinders their large-scale commercialization. Summary of the Invention

[0005] Based on the aforementioned problems, it is necessary to provide a platinum-conductive diamond composite anti-reverse catalyst and its preparation method, as well as a fuel cell using the platinum-conductive diamond composite anti-reverse catalyst.

[0006] A method for preparing a platinum-conductive diamond composite anti-reverse electrode catalyst includes the following steps: S1: Provide one or more of the following as nanoparticle substrates: nanodiamond particles, nanoboron nitride, nanoboron carbide, metal oxide nanoparticles, metal carbide nanoparticles, metal nitride nanoparticles, and silicon-based nanoparticles; One or more of nanodiamond particles, nanoboron nitride, nanoboron carbide, metal oxide nanoparticles, metal carbide nanoparticles, metal nitride nanoparticles, and silicon-based nanoparticles are provided, and a porous structure is formed on the surface of at least a portion of the nanoparticles to obtain a nanoparticle substrate. S2: Conductive diamond particles are assembled on the nanoparticle substrate by high temperature and high pressure method or chemical vapor deposition method to obtain nano blue diamond assembly; S3: At least one of carbon-supported platinum nanoparticles and carbon-supported platinum alloy nanoparticles is mixed with the nano-blue diamond assembly to obtain a platinum-conductive diamond composite anti-reverse electrode catalyst, or; A carbon-based support is provided, and the nano-blue diamond assembly is mixed with the carbon-based support to obtain a mixed particulate support. At least one of platinum nanoparticles and platinum alloy nanoparticles is provided, and the platinum nanoparticles and / or platinum alloy nanoparticles are supported on the surface of the mixed particulate support to obtain a platinum-conductive diamond composite anti-reverse polarization catalyst, or; At least one of platinum nanoparticles and platinum alloy nanoparticles is provided, and the platinum nanoparticles and / or platinum alloy nanoparticles are supported on the surface of the nano-blue diamond assembly to obtain a platinum-conductive diamond composite anti-reverse electrode catalyst.

[0007] In one embodiment, step S0 is further included, which includes: Carbon-containing explosives are converted into diamonds by an explosion method to obtain intermediate products. The intermediate products are then screened to separate nanodiamond particles, or... Diamond crystals are grown by high temperature and high pressure method or chemical vapor deposition method, and the diamond crystals are then crushed into micro-nano-scale particles by physical means to obtain nano-diamond particles.

[0008] In one embodiment, step S1 includes: providing one or more of nanodiamond particles, nanoboron nitride, nanoboron carbide, metal oxide nanoparticles, metal carbide nanoparticles, metal nitride nanoparticles, and silicon-based nanoparticles, and forming a porous structure on the surface of at least a portion of the nanoparticles by means of calcination, chemical etching, plasma etching, or laser etching to obtain a nanoparticle substrate.

[0009] In one embodiment, in step S2, after assembling the conductive diamond particles on the nanoparticle substrate by chemical vapor deposition, the carbon source and boron source are turned off, while keeping other parameters unchanged, and the reaction is carried out for 1-30 minutes under hydrogen gas to form CH bonds on the surface of the conductive diamond particles, thereby obtaining the nano-blue diamond assembly.

[0010] In one embodiment, in step S2, after assembling the conductive diamond particles on the nanoparticle substrate, the particles are treated with 98% concentrated sulfuric acid at 80°C for 1 hour to form ether bonds or aldehyde groups on the surface of the conductive diamond particles, thereby obtaining the nano-blue diamond assembly.

[0011] In one embodiment, in step S2, after assembling the conductive diamond particles on the nanoparticle substrate by chemical vapor deposition, the particles are immersed in hydrogen peroxide with a concentration of 30%-50% and irradiated with 254nm ultraviolet light for 1 hour to form hydroxyl groups on the surface of the conductive diamond particles, thereby obtaining the nano-blue diamond assembly.

[0012] In one embodiment, the carbon-based support includes at least one of carbon black, graphite, graphene, carbon nanotubes, carbon nanowires, fullerenes, carbon gels, ordered mesoporous carbon, disordered mesoporous carbon, carbon fibers, and boron carbide.

[0013] In one embodiment, the silicon-based nanoparticles include at least one of nano-silicon nitride, nano-silicon carbide, and nano-silicon dioxide.

[0014] In one embodiment, the metal oxide nanoparticles include one or more of ferric oxide, iron tetroxide, bismuth oxide, zirconium oxide, chromium oxide, and nickel oxide.

[0015] In one embodiment, the metal carbide nanoparticles include one or more of vanadium carbide, zirconium carbide, chromium carbide, molybdenum carbide, niobium carbide, titanium carbide, tungsten carbide, and tantalum carbide.

[0016] In one embodiment, the metal nitride nanoparticles include one or more of titanium nitride and titanium carbonitride.

[0017] A platinum-conductive diamond composite anti-reverse electrode catalyst is prepared using any one of the above-described methods for preparing platinum-conductive diamond composite anti-reverse electrode catalysts.

[0018] A fuel cell includes an anode and a cathode, wherein the catalyst layer of the anode and / or cathode uses the platinum-conductive diamond composite anti-reverse catalyst described in any of the preceding claims.

[0019] The beneficial effects of this invention are: Using conductive diamond as a carrier or catalyst additive, preferential water electrolysis under high reverse electrode potential can be achieved to suppress carbon corrosion. Compared with expensive and rare precious metals such as iridium and ruthenium and their oxides, conductive diamond can be artificially synthesized, enabling large-scale commercial applications. This makes the promotion and application of fuel cells more likely and is also inexpensive. Platinum and platinum alloy nanoparticles are supported by combining nano-blue diamond assemblies with carbon-based supports, or by directly supporting platinum and platinum alloy nanoparticles with nano-blue diamond assemblies. This results in high durability of the catalyst and provides mechanical strength of the fuel cell catalyst layer throughout its entire life cycle. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0021] Figure 1 This is a flowchart of a method for preparing a platinum-conductive diamond composite anti-reverse electrode catalyst in one embodiment of the present invention.

[0022] Figure 2 This is a schematic diagram of the structure of a platinum-conductive diamond composite anti-reverse electrode catalyst according to an embodiment of the present invention.

[0023] Figure 3 This is a schematic diagram of the structure of a platinum-conductive diamond composite anti-reverse electrode catalyst according to another embodiment of the present invention.

[0024] Figure 4 This is a schematic diagram of the structure of a platinum-conductive diamond composite anti-reverse electrode catalyst according to another embodiment of the present invention.

[0025] Figure 5 for Figure 2 , Figure 3 , Figure 4 The structural annotation diagram in the text.

[0026] Figure 6 This is a Fourier transform infrared spectrum of conductive diamond according to an embodiment of the present invention.

[0027] Figure 7 This is a scanning electron microscope (SEM) image of a platinum-conductive diamond composite anti-reverse electrode catalyst according to an embodiment of the present invention.

[0028] Figure 8 This is the Raman spectrum of the conductive diamond in the platinum-conductive diamond composite catalyst of the present invention.

[0029] Figure 9This is a schematic diagram illustrating the anti-reverse polarization effect of a platinum-conductive diamond composite anti-reverse polarization catalyst according to an embodiment of the present invention.

[0030] Figure 10 This is a comparison diagram of the water oxidation effect of a platinum-conductive diamond composite anti-reverse electrode catalyst and a conventional platinum-carbon catalyst under high potential according to an embodiment of the present invention.

[0031] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0032] The present invention provides a platinum-conductive diamond composite anti-reverse electrode catalyst, which in one embodiment includes: a support and an active material, wherein the active material is supported on the support.

[0033] The carrier includes a nano-blue diamond assembly, or the carrier includes a nano-blue diamond assembly and a carbon-based carrier.

[0034] The active material includes at least one of platinum and platinum alloys.

[0035] The nano-blue diamond assembly includes a nanoparticle substrate and a layer of conductive diamond particles formed on the surface of the nanoparticle substrate.

[0036] In this embodiment, the nano-blue diamond assembly is used as a carrier and hybrid carrier to support platinum and platinum alloys.

[0037] Furthermore, the present invention also provides another platinum-conductive diamond composite anti-reverse electrode catalyst, in another embodiment of which the catalyst comprises a main catalyst and a co-catalyst.

[0038] The main catalyst includes at least one of carbon-supported platinum nanoparticles and carbon-supported platinum alloy nanoparticles, and the co-catalyst includes a nano-blue diamond assembly.

[0039] The nano-blue diamond assembly includes a nanoparticle substrate and a layer of conductive diamond particles formed on the surface of the nanoparticle substrate.

[0040] In this embodiment, the nano-blue diamond composite is used as a catalyst promoter, mixed with carbon-supported platinum and / or carbon-supported platinum alloy as a catalyst.

[0041] The present invention provides a method for preparing the above two platinum-conductive diamond composite anti-reverse polarization catalysts, the method comprising the following steps: Step S1: Provide one or more of the following as nanoparticle substrates: nanodiamond particles, nanoboron nitride, nanoboron carbide, metal oxide nanoparticles, metal carbide nanoparticles, metal nitride nanoparticles, and silicon-based nanoparticles; A nanoparticle substrate is obtained by providing one or more of the following: nanodiamond particles, nanoboron nitride, nanoboron carbide, metal oxide nanoparticles, metal carbide nanoparticles, metal nitride nanoparticles, and silicon-based nanoparticles, and forming a porous structure on the surface of at least a portion of the nanoparticles.

[0042] In step S1, the following can be obtained: ① A nanoparticle substrate consisting of one or more mixed particles selected from nanodiamond particles, nanoboron nitride, nanoboron carbide, metal oxide nanoparticles, metal carbide nanoparticles, metal nitride nanoparticles, and silicon-based nanoparticles; ② A nanoparticle substrate consisting of one or more mixed particles selected from nanodiamond particles, nanoboron nitride, nanoboron carbide, metal oxide nanoparticles, metal carbide nanoparticles, metal nitride nanoparticles, and silicon-based nanoparticles, with pore-forming treatment applied to the surface of all nanoparticles; ③ A nanoparticle substrate consisting of one or more mixed particles selected from nanodiamond particles, nanoboron nitride, nanoboron carbide, metal oxide nanoparticles, metal carbide nanoparticles, metal nitride nanoparticles, and silicon-based nanoparticles, with pore-forming treatment applied to the surface of a portion of the nanoparticles and no pore-forming treatment applied to the remaining nanoparticles, and the two portions of nanoparticles mixed together.

[0043] To create pores on the surface of nanoparticles, for example, in one embodiment, step S1 includes: providing one or more of nanodiamond particles, nanoboron nitride, nanoboron carbide, metal oxide nanoparticles, metal carbide nanoparticles, metal nitride nanoparticles, and silicon-based nanoparticles, and forming a porous structure on the surface of at least a portion of the nanoparticles by means of calcination, chemical etching, plasma etching, or laser etching to obtain a nanoparticle substrate.

[0044] For example, the silicon-based nanoparticles include one or more of nano-silicon nitride, nano-silicon carbide, and nano-silicon dioxide.

[0045] For example, the metal oxide nanoparticles include one or more of ferric oxide, iron tetroxide, bismuth oxide, zirconium oxide, chromium oxide, and nickel oxide.

[0046] For example, the metal carbide nanoparticles include one or more of vanadium carbide, zirconium carbide, chromium carbide, molybdenum carbide, niobium carbide, titanium carbide, tungsten carbide, and tantalum carbide.

[0047] For example, the metal nitride nanoparticles include one or more of titanium nitride and titanium carbonitride.

[0048] The aforementioned nanodiamond particles, nanoboron nitride, nanoboron carbide, metal oxide nanoparticles, metal carbide nanoparticles, metal nitride nanoparticles, and silicon-based nanoparticles can be obtained commercially or prepared in-house.

[0049] For example, if nanodiamond particles are used as the nanoparticle raw material in step S1, the preparation method of the platinum-conductive diamond composite anti-reverse polarization catalyst of the present invention further includes step S0 to prepare nanodiamond particles. In one embodiment, step S0 includes: Carbon-containing explosives are converted into diamonds by an explosion method to obtain intermediate products. These intermediate products are then screened to separate nanodiamond particles.

[0050] The principle of the explosive method for converting carbon into diamond is as follows: using carbon-containing explosives in negative oxygen balance as raw materials, during detonation, the oxygen in the explosive molecules is insufficient to oxidize all the carbon into CO or CO2. Therefore, free carbon exists in the detonation zone. Under the high pressure and high temperature of the detonation zone, some of the free carbon is converted into diamond. The product includes not only diamond but also impurities such as graphite and amorphous carbon. To obtain the desired diamond powder, it needs to be screened and separated. The separated nanodiamond particles have a diameter of less than 20 nm. In the preferred embodiment of this invention, nanodiamond particles with a diameter of less than 10 nm are screened out.

[0051] In one embodiment, in step S0, impurities in the intermediate product are removed by acid washing and oxidation to separate the nanodiamond particles. For example, boiling and heating with concentrated sulfuric acid and concentrated nitric acid can remove impurities such as graphite and most of the amorphous carbon.

[0052] In another embodiment, step S0 includes: Diamond crystals are grown by high temperature and high pressure method or chemical vapor deposition method, and the diamond crystals are then crushed into micro-nano-scale particles by physical means to obtain nano-diamond particles.

[0053] The high temperature and high pressure method uses a catalyst to convert carbon sources such as graphite into diamond under high temperature and high pressure conditions. Chemical vapor deposition methods, including hot filament deposition and microwave deposition, involve introducing a mixture of carbon-containing gas and hydrogen into a vacuum chamber. Under high temperature and pressure below standard atmospheric pressure, the carbon-containing gas and hydrogen are excited and dissociated, thereby generating diamond.

[0054] Large diamond crystals are grown using high temperature and high pressure methods or chemical vapor deposition. These large diamond crystals are then pulverized into micro- and nano-sized particles using physical means such as crushing and grinding.

[0055] For example, a high-temperature, high-pressure method is used to obtain conductive diamond particles from a catalyst / graphite / boron source under high temperature and high pressure (above 500°C, exceeding 10 GPa) conditions via a hydraulic press. These particles are then physically broken down to obtain small conductive diamond particles. Alternatively, conductive small diamond particles can be directly prepared using a high-temperature, high-pressure method (above 500°C, exceeding 10 GPa), resulting in diamond particles with a diameter of 1 nm to 1 μm. In a preferred embodiment of this invention, these particles are pulverized into nanodiamond particles with a diameter of less than 15 nm.

[0056] Furthermore, in one embodiment, after step S1 and before step S2, a dispersion step is included, in which the nanoparticles obtained in S1 are dispersed into powder by physical means.

[0057] Step S2: Conductive diamond particles are assembled on the nanoparticle substrate using a high-temperature, high-pressure method or a chemical vapor deposition method to obtain a nano-blue diamond assembly.

[0058] Using the three nanoparticle substrates in step S1 above as substrate materials, a conductive diamond particle coating layer is formed on their surface, which is the nano-blue diamond assembly. Among them, when ① (non-porous nanoparticle substrate) is used as the substrate material, conductive diamond particles are formed on its surface. When ② (porous nanoparticle substrate) and ③ (partially porous nanoparticle substrate mixed with partially non-porous nanoparticle substrate) are used as substrate materials, conductive diamond particles are formed on their surface and inside the pores.

[0059] In one embodiment, the conductive diamond particles are assembled onto the nanoparticle substrate using hot-wire chemical vapor deposition (HFCVD) to form a conductive nanodiamond coating. The parameters for HFCVD are: abutment temperature 500-800℃, hot-wire temperature 180-2400℃, gas pressure 1-5 kPa, hydrogen gas flow rate 100-1000 sccm, methane flow rate 1-20 sccm, borane flow rate 1-20 sccm, and growth time ≥ 10 min. The thickness of the formed conductive nanodiamond coating is 1 nm-10 μm; the thicker the coating, the longer the reaction time.

[0060] In another embodiment, the conductive diamond particles are assembled onto the nanoparticle substrate using microwave plasma chemical vapor deposition (MPCVD). The parameters of MPCVD are: microwave power 500-3000 W, hydrogen gas flow rate 100-1000 sccm, methane flow rate 1-20 sccm, borane flow rate 1-10 sccm, stage temperature 500-700℃, gas pressure 4-6 kPa, and growth time 3-10 h. The thickness of the formed conductive diamond nanolayer is 1 nm-10 μm; the thicker the layer, the longer the reaction time.

[0061] like Figure 6 The image shows the diffuse reflectance Fourier transform infrared spectrum of the conductive diamond in the catalyst of one embodiment of the present invention, which is type IIb boron-doped conductive diamond.

[0062] Figure 7 This is a schematic diagram of the structural morphology of conductive diamond in a catalyst according to an embodiment of the present invention, which has a porous structure.

[0063] As some preferred embodiments, after assembling conductive diamond particles on the surface of a nanoparticle substrate, the surface is then treated to make it hydrophobic or hydrogen-absorbing. The modified product is the nano-blue diamond assembly.

[0064] To enable it to absorb hydrogen, example (1) is provided: Conductive diamond particles are assembled on the nanoparticle substrate by high temperature and high pressure method or chemical vapor deposition method. Then, the nano-blue diamond catalyst is treated with 98% concentrated sulfuric acid at 80°C for 1 hour to form ether bonds, aldehyde groups or ketone groups on the surface of the nano-blue diamond catalyst, thus obtaining the nano-blue diamond assembly.

[0065] To enable it to absorb hydrogen, Example (2) is provided: Conductive diamond particles are assembled on the nanoparticle substrate by high temperature and high pressure method or chemical vapor deposition method. Then, the particles are immersed in hydrogen peroxide with a concentration of 30%-50% and irradiated with 254nm ultraviolet light for 1 hour to form hydroxyl groups on the surface of the conductive diamond particles, thus obtaining the nano-blue diamond assembly.

[0066] To make it hydrophobic, an example (3) is provided: Conductive diamond particles were assembled on a nanoparticle substrate by chemical vapor deposition. Then, the carbon and boron sources were turned off, and other parameters were kept constant. The reaction was carried out for 1-30 minutes under hydrogen gas to form CH bonds on the surface of the conductive diamond particles, thus obtaining a nano-blue diamond assembly.

[0067] The above methods endow the surface of the nano-blue diamond composite with the properties of adsorbing hydrogen or hydrophobicity. When used as a carrier or catalyst additive in fuel cells, the hydrogen-adsorbing nano-blue diamond composite accelerates the decomposition of hydrogen into hydrogen ions on the anode side, facilitating their transfer to the cathode. The hydrophobic nano-blue diamond composite, by making it hydrophobic, allows water to be quickly transferred away, enabling oxygen to efficiently contact the catalyst for reaction, and continuously transferring hydrogen, thereby improving the overall efficiency of the fuel cell.

[0068] Step S3: Example (4) At least one of carbon-supported platinum nanoparticles and carbon-supported platinum alloy nanoparticles is provided and mixed with the nano-blue diamond assembly to obtain a platinum-conductive diamond composite anti-reverse electrode catalyst.

[0069] In this embodiment, the nano-blue diamond assembly is used as a catalyst additive to form: a1. A mixture of nano-blue diamond composites and carbon-supported platinum nanoparticles; a2. A mixture of nano-blue diamond composites and carbon-supported platinum alloy nanoparticles; a3. Nano-blue diamond composite with carbon-supported platinum and carbon-supported platinum alloy nanoparticles.

[0070] In this embodiment, the three types a1, a2, and a3 mentioned above are the platinum-conductive diamond composite anti-reverse electrode catalysts of the present invention.

[0071] Figure 2 The diagram shown is a schematic representation of the platinum-conductive diamond composite anti-reverse electrode catalyst in this embodiment. Please refer to [link to relevant documentation]. Figure 5 As Figure 2 The accompanying figures are captioned as follows: (1) is a nano-blue diamond assembly, (2) is platinum nanoparticles and / or platinum alloy nanoparticles, and (3) is a carbon-based carrier.

[0072] Example (5) A carbon-based support is provided, and the nano-blue diamond assembly is mixed with the carbon-based support to obtain a mixed particulate support. At least one of platinum nanoparticles and platinum alloy nanoparticles is provided, and the platinum nanoparticles and / or platinum alloy nanoparticles are supported on the surface of the mixed particulate support to obtain a platinum-conductive diamond composite anti-reverse electrode catalyst.

[0073] In this embodiment, the nano-blue diamond assembly is used as a hybrid carrier to form: b1. Nano-blue diamond composite - carbon-based hybrid carrier, jointly supporting platinum nanoparticles; b2: Nano-blue diamond composite - carbon-based hybrid carrier, jointly supporting platinum alloy nanoparticles; b3: Nano-blue diamond composite - carbon-based hybrid carrier, jointly supporting platinum nanoparticles and platinum alloy nanoparticles.

[0074] In this embodiment, b1, b2, and b3 are the platinum-conductive diamond composite anti-reverse electrode catalysts of the present invention.

[0075] Figure 3 The diagram shown is a schematic representation of the platinum-conductive diamond composite anti-reverse electrode catalyst in this embodiment. Please refer to [link to relevant documentation]. Figure 5 As Figure 3 The accompanying figures are captioned as follows: (1) is a nano-blue diamond assembly, (2) is platinum nanoparticles and / or platinum alloy nanoparticles, and (3) is a carbon-based carrier.

[0076] Example (6) At least one of platinum nanoparticles and platinum alloy nanoparticles is provided, and the platinum nanoparticles and / or platinum alloy nanoparticles are supported on the surface of the nano-blue diamond assembly to obtain a platinum-conductive diamond composite anti-reverse electrode catalyst.

[0077] In this embodiment, the nano-blue diamond assembly is used as the sole carrier, forming: c1: Nano-blue diamond composite supporting platinum nanoparticles; c2: Nano-blue diamond composite supporting platinum alloy nanoparticles; c3: The nano-blue diamond composite carries platinum nanoparticles and platinum alloy nanoparticles.

[0078] In this embodiment, c1, c2, and c3 are the platinum-conductive diamond composite anti-reverse electrode catalysts of the present invention.

[0079] Figure 4 The diagram shown is a schematic representation of the platinum-conductive diamond composite anti-reverse electrode catalyst in this embodiment. Please refer to [link to relevant documentation]. Figure 5 As Figure 4 The accompanying figures are captioned as follows: (1) is a nano-blue diamond assembly, (2) is platinum nanoparticles and / or platinum alloy nanoparticles, and (3) is a carbon-based carrier.

[0080] For example, the aforementioned carbon-based supports include at least one of carbon black, graphite, graphene, carbon nanotubes, carbon nanowires, fullerenes, carbon gels, ordered mesoporous carbon, disordered mesoporous carbon, carbon fibers, and boron carbide.

[0081] in, Figure 8 The image shows the Raman spectrum of conductive diamond in a platinum-conductive diamond composite anti-reverse electrode catalyst according to an embodiment of the present invention. Its high sp3 carbon structure provides the material with high durability and oxidation resistance.

[0082] Figure 9The electrochemical active area of ​​the platinum-conductive diamond composite anti-reverse electrode catalyst in one embodiment of the present invention was compared before and after 2000 seconds of 2V reverse electrode treatment. After 2000 seconds of 2V reverse electrode treatment, the electrochemical active area of ​​the catalyst of the present invention decreased by only 6%, that is, the catalyst structure did not change significantly after reverse electrode treatment. This shows that the catalyst of the present invention has extremely strong anti-reverse electrode durability and can maintain the mechanical strength of the catalyst layer.

[0083] Figure 10 This diagram illustrates the effect of a platinum-conductive diamond composite anti-reverse electrode catalyst of an embodiment of the present invention on promoting water oxidation at high potential. Traditionally used iridium catalysts have a water oxidation initiation potential of 1.35-1.4V, while the water oxidation initiation potential of the catalyst of the present invention is 1.5V, which is lower than that of platinum catalysts (1.65-1.7V). Therefore, under high potential and reverse electrode conditions, the catalyst of the present invention can preferentially promote water oxidation to inhibit the oxidative corrosion of the carbon-based support used in the composite catalyst.

[0084] The beneficial effects of this invention are as follows: Using conductive diamond as a carrier or catalyst additive, preferential water electrolysis under high reverse potential can be achieved to suppress carbon corrosion. Compared with expensive and rare precious metals such as iridium and ruthenium and their oxides, conductive diamond can be artificially synthesized, enabling large-scale commercial applications. This makes the promotion and application of fuel cells more likely and is also inexpensive.

[0085] Platinum and platinum alloy nanoparticles are supported by combining nano-blue diamond assemblies with carbon-based supports, or by directly supporting platinum and platinum alloy nanoparticles with nano-blue diamond assemblies. This results in high durability of the catalyst and provides mechanical strength of the fuel cell catalyst layer throughout its entire life cycle.

[0086] In some preferred embodiments, the present invention also has the following advantages: 1. Forming a porous structure on the surface of the nanoparticles serving as the substrate gives it a huge specific surface area, which increases the contact surface of the conductive diamond and makes its anti-reverse polarity performance better.

[0087] 2. By modifying the surface of the nano-blue diamond assembly and selecting hydrophilic groups such as hydroxyl groups, a selective humidification effect on the catalyst can be achieved.

[0088] The present invention provides a fuel cell comprising an anode and a cathode, wherein the catalyst layer of the anode and / or cathode uses the platinum-conductive diamond composite anti-reverse catalyst described above.

[0089] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0090] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A method for preparing a platinum-conductive diamond composite anti-reverse polarization catalyst, characterized in that, Includes the following steps: S1: Provide one or more of the following as nanoparticle substrates: nanodiamond particles, nanoboron nitride, nanoboron carbide, metal oxide nanoparticles, metal carbide nanoparticles, metal nitride nanoparticles, and silicon-based nanoparticles; One or more of nanodiamond particles, nanoboron nitride, nanoboron carbide, metal oxide nanoparticles, metal carbide nanoparticles, metal nitride nanoparticles, and silicon-based nanoparticles are provided, and a porous structure is formed on the surface of at least a portion of the nanoparticles to obtain a nanoparticle substrate. S2: Conductive diamond particles are assembled on the nanoparticle substrate by high temperature and high pressure method or chemical vapor deposition method to obtain nano blue diamond assembly; S3: At least one of carbon-supported platinum nanoparticles and carbon-supported platinum alloy nanoparticles is mixed with the nano-blue diamond assembly to obtain a platinum-conductive diamond composite catalyst, or; A carbon-based support is provided, and the nano-blue diamond assembly is mixed with the carbon-based support to obtain a mixed particulate support. At least one of platinum nanoparticles and platinum alloy nanoparticles is provided, and the platinum nanoparticles and / or platinum alloy nanoparticles are supported on the surface of the mixed particulate support to obtain a platinum-conductive diamond composite catalyst, or; At least one of platinum nanoparticles and platinum alloy nanoparticles is provided, and the platinum nanoparticles and / or platinum alloy nanoparticles are supported on the surface of the nano-blue diamond assembly to obtain a platinum-conductive diamond composite catalyst.

2. The preparation method of the platinum-conductive diamond composite anti-reverse polarization catalyst according to claim 1, characterized in that, Step S1 includes: providing one or more of nanodiamond particles, nanoboron nitride, nanoboron carbide, metal oxide nanoparticles, metal carbide nanoparticles, metal nitride nanoparticles, and silicon-based nanoparticles, and forming a porous structure on the surface of at least a portion of the nanoparticles by means of calcination, chemical etching, plasma etching, or laser etching to obtain a nanoparticle substrate.

3. The preparation method of the platinum-conductive diamond composite anti-reverse polarization catalyst according to claim 1, characterized in that, In step S2, after assembling the conductive diamond particles on the nanoparticle substrate by chemical vapor deposition, the carbon and boron sources are turned off, and other parameters are kept constant. The reaction is carried out for 1-30 minutes under hydrogen gas to form CH bonds on the surface of the conductive diamond particles, thus obtaining the nano-blue diamond assembly.

4. The preparation method of the platinum-conductive diamond composite anti-reverse polarization catalyst according to claim 1, characterized in that, In step S2, after assembling the conductive diamond particles on the nanoparticle substrate, they are treated with 98% concentrated sulfuric acid at 80°C for 1 hour to form ether bonds or aldehyde groups on the surface of the conductive diamond particles, thus obtaining the nano-blue diamond assembly.

5. The preparation method of the platinum-conductive diamond composite anti-reverse polarization catalyst according to claim 1, characterized in that, In step S2, after assembling the conductive diamond particles on the nanoparticle substrate, the particles are immersed in hydrogen peroxide with a concentration of 30%-50% and irradiated with 254nm ultraviolet light for 1 hour to form hydroxyl groups on the surface of the conductive diamond particles, thereby obtaining the nano-blue diamond assembly.

6. The preparation method of the platinum-conductive diamond composite anti-reverse polarization catalyst according to claim 1, characterized in that, The carbon-based carriers include at least one of carbon black, graphite, graphene, carbon nanotubes, carbon nanowires, fullerenes, carbon gels, ordered mesoporous carbon, disordered mesoporous carbon, carbon fibers, and boron carbide.

7. The preparation method of the platinum-conductive diamond composite anti-reverse polarization catalyst according to claim 1, characterized in that, The silicon-based nanoparticles include at least one of nano-silicon nitride, nano-silicon carbide, and nano-silicon dioxide.

8. The preparation method of the platinum-conductive diamond composite anti-reverse polarization catalyst according to claim 1, characterized in that, The metal oxide nanoparticles include one or more of the following: ferric oxide, iron tetroxide, bismuth oxide, zirconium oxide, chromium oxide, and nickel oxide.

9. The preparation method of the platinum-conductive diamond composite anti-reverse polarization catalyst according to claim 1, characterized in that, The metal carbide nanoparticles include one or more of vanadium carbide, zirconium carbide, chromium carbide, molybdenum carbide, niobium carbide, titanium carbide, tungsten carbide, and tantalum carbide.

10. The preparation method of the platinum-conductive diamond composite anti-reverse polarization catalyst according to claim 1, characterized in that, The metal nitride nanoparticles include one or more of titanium nitride and titanium carbide nitride.

11. A platinum-conductive diamond composite anti-reverse polarization catalyst, characterized in that, It was prepared using the method for preparing the platinum-conductive diamond composite anti-reverse polarization catalyst according to any one of claims 1-10.

12. A fuel cell, characterized in that, It includes an anode and a cathode, wherein the catalyst layer of the anode and / or cathode uses the platinum-conductive diamond composite anti-reverse electrode catalyst as described in any one of claims 1-10.